Symptom experience of adverse drug reaction among male and female patients with newly diagnosed pulmonary tuberculosis in Thailand - Apichaya Thontham; Rapin Polsook (Belitung Nursing Journal, 2021)
Background: Patients with newly diagnosed pulmonary tuberculosis often suffer from adverse drug reaction symptoms, which leads to the automatic discontinuation of anti-tuberculosis drugs. Thus, understanding symptom experience of adverse drug reactions is necessary. Objective: This study aimed to examine differences in symptoms experienced in four dimensions: presence, frequency, severity, and distress of adverse drug reactions, between male and female patients. Methods: This was a quantitative survey with a cross-sectional design, with data collected between January and April 2020. A total of 394 patients with newly diagnosed pulmonary tuberculosis was selected through a purposive sampling technique. The symptom experiences of adverse drug reactions were measured using a validated instrument. Data were analyzed using mean, standard deviation, and independent t-test. Results: The most commonly reported symptom was itchiness (24.1% in males and 34.9% in females). Vomiting occurred as the most frequent symptom among males (x̅ ± SD = 2.73 ± .88), and fatigue was found to be the most severe and distressing symptom across male patients (x̅ ± SD = 2.50 ± 1.61 and 2.06 ± 1.30, respectively). In contrast, yellowing of the eyes and skin was most frequent and severe among females (x̅ ± SD = 3.17 ± .75 and 3.83 ± 1.47, respectively). In addition, flu-like symptoms were evaluated as the most distressing symptom for female patients (x̅ ± SD = 2.80 ± 1.09). The symptom burdens of the females ranged significantly and reached higher than those of the male patients at a p-value of .05 (t = 3.33). Conclusion: Females taking anti-tuberculosis drugs should be carefully monitored to deal with adverse drug reaction symptoms. This finding would help to decrease the severity of disease and improve their quality of life.